URBAN TRANSFORMATION OF KHERSON AT THE TURN OF THE 19TH AND 20TH CENTURIES: ELECTRIC TRANSPORT AS A MECHANISM OF URBAN MODERNIZATION (Південний архів (історичні науки), 2026)
The purpose of this article is to analyze the processes of organization, evolution, and development of Kherson’s urban space at the beginning of the 20th century in the context of modernization processes in southern Ukraine, in particular through the attempt to introduce electric trams under an agreement with Italian citizen V.F. Bоsalini. The article compares Kherson with its neighboring cities, Odesa and Mykolaiv, where tramways were implemented, which allows us to assess the peculiarities of local urban transformation. Methodologically, the study is based on a comprehensive historical and urban analysis using a cybernetic approach to urban space management and the theory of urban system modernization. It uses an analysis of archival sources, in particular a comparative analysis of the experience of other southern cities in the field of tramway implementation and technological modernization. The scientific novelty of the article lies in the comprehensive combination of two theoretical concepts: cybernetically oriented urban space management and the theory of modernization with a European orientation. Another scientific novelty is that we introduce new archival documents into scientific circulation. The main content of the article shows that the agreement with Bоsalinі contained a potential management system integrating transport, energy, and social infrastructure that corresponded to the principles of feedback, hierarchy, and adaptability. However, the project remained unrealized, which fundamentally distinguishes the modernization of Kherson and Mykolaiv from Odesa, where tramways contributed to the formation of integrated cybernetic systems of urban management and socio-economic dynamics. The article also highlights the role of foreign entrepreneurs as agents of European modernization who could have introduced advanced European technical standards, organizational models, and urban practices in Kherson. The conclusions emphasize that the lack of practical implementation of the project limited Kherson’s modernization potential, leaving its urban space in a state of potential but incomplete transformation.
Keywords: Kherson, tramization, urban space modernization, Europeanization, urbanism, Southern Ukraine